Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T16:07:09+02:00
A) 3/x-2 = 4/2x + 1
założenia:
x-2≠0 czyli x≠2 i x≠0
3/x-2 = 4/2x + 1
3/(x-2)=2/x +1
3/(x-2)=(2+x)/x
3/(x-2)-(2+x)/x=0
(3x-(2+x)(x-2)/(x(x-2))=0
3x-(2+x)(x-2)=0
-x²+3x+4=0
Δ=9+16=25
√Δ=5
x₁=(-3-5)/(-2)=4
x₂=(-3+5)/(-2)=-2

b) 2/3 = 3x+2/2x-2
Założenia:
2x-2≠0, czyli x≠1
2/3 = 3x+2/2x-2
2/3=3x+2/(2(x-1))
2/3=3x+1/(x-1) |*(x-1) |*3
2(x-1)=9x(x-1)+3
2x-2=9x²-9x+3
9x²-11x+5=0
Δ=121-180 <0
Brak rozwiązań

c) 6x-1/x+1 = 2.3/1,2
założenia
x≠-1
6x-1/x+1 = (23/10)/(12/10)
6x-1/x+1 = 23/12
12(6x-1)=23(x+1)
72x-12=23x+23
49x=35
x=35/49
x=5/7

d) -x/3x-1 = 2x/1-6x
Założenia:
x≠1/3 i x≠1/6
-x(1-6x)=2x(3x-1)
-x-6x²=6x²-2x
-x=-2x
x=0
2 2 2